2009
DOI: 10.1073/pnas.0812043106
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of F-box genes in plants: Different modes of sequence divergence and their relationships with functional diversification

Abstract: F-box proteins are substrate-recognition components of the Skp1-Rbx1-Cul1-F-box protein (SCF) ubiquitin ligases. In plants, F-box genes form one of the largest multigene superfamilies and control many important biological functions. However, it is unclear how and why plants have acquired a large number of F-box genes. Here we identified 692, 337, and 779 F-box genes in Arabidopsis, poplar and rice, respectively, and studied their phylogenetic relationships and evolutionary patterns. We found that the plant F-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
311
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(327 citation statements)
references
References 36 publications
11
311
2
3
Order By: Relevance
“…Plant FBX genes constitute a large family of genes (approximately 800 in F. vesca and approximately 690 in Arabidopsis) and can be classified into several distinct subfamilies based on domain structures (Kuroda et al, 2002;Xu et al, 2009). To investigate which specific FBX gene subfamilies are regulated by the clustered miRFBXs and deduce their potential functions, we performed phylogenetic analysis using all the FBX genes from Arabidopsis (691 genes; Xu et al, 2009) and the set of 96 F. vesca FBX genes targeted by the clustered miFBXs (Supplemental Table S6).…”
Section: Mirfbxs Mostly Target the Conserved F-box Domainmentioning
confidence: 99%
See 3 more Smart Citations
“…Plant FBX genes constitute a large family of genes (approximately 800 in F. vesca and approximately 690 in Arabidopsis) and can be classified into several distinct subfamilies based on domain structures (Kuroda et al, 2002;Xu et al, 2009). To investigate which specific FBX gene subfamilies are regulated by the clustered miRFBXs and deduce their potential functions, we performed phylogenetic analysis using all the FBX genes from Arabidopsis (691 genes; Xu et al, 2009) and the set of 96 F. vesca FBX genes targeted by the clustered miFBXs (Supplemental Table S6).…”
Section: Mirfbxs Mostly Target the Conserved F-box Domainmentioning
confidence: 99%
“…8G). FBX genes encode the substrate-recognition subunits of the SCF (for S-phase kinase associated protein1-Cullin-F Box) ubiquitin ligases and constitute one of the largest gene families, with 820 members in F. vesca (Xu et al, 2009;Hollender et al, 2014). FBX proteins regulate diverse biological processes and were grouped into two general types based on whether they function in conserved processes, such as embryogenesis and circadian rhythms, or relatively specialized processes, such as pollen recognition and pathogen response (Xu et al, 2009).…”
Section: The Lg3 Mirfbx Cluster Recently Evolved From Fbx Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 186 genes with exons/UTRs affected by indels (Supplemental Table 9) could have changed/disrupted expression or functions. F-box genes encode subunits of E3 ubiquitin ligases that are involved in physiological and environmental responses and differ dramatically in gene number among A. thaliana, poplar, and rice (Xu et al 2009). We found that eight F-box genes are absent from Ler (Supplemental Table 8) and 16 other F-box genes are partially affected (Supplemental Table 9), suggesting that these rapidly evolving genes are highly unstable even within the Arabidopsis species.…”
Section: Detection Of Large Indels and Cnvsmentioning
confidence: 99%